Application Research of SQLite Database in Modern Information Management of Coal Mine - TAO Ye (Gong-kuang zidonghua, 2011)
In view of problems of complex operation and high maintenance cost existed in application of large databases in modern information management of coal mine, the paper proposed a scheme of modern information management of coal mine by use of SQLite database. It introduced basic structure and characteristics of SQLite database and gave simulation analysis of the scheme. The test result showed that SQLite database can fully play advantages of high efficiency and useability for portal website and office automation system in modern information management of coal mine, but SQLite database has certain limitation for gas monitoring and control system which needs a lot of concurrent operation.